Zoonotic disease risk perceptions in the British veterinary profession - Robin, C.; Bettridge, Judy M.; McMaster, F. (Elsevier, 2017)
In human and veterinary medicine, reducing the risk of occupationally-acquired infections relies on effective infection prevention and control practices (IPCs). In veterinary medicine, zoonoses present a risk to practitioners, yet little is known about how these risks are understood and how this translates into health protective behaviour. This study aimed to explore risk perceptions within the British veterinary profession and identify motivators and barriers to compliance with IPCs. A cross-sectional study was conducted using veterinary practices registered with the Royal College of Veterinary Surgeons. Here we demonstrate that compliance with IPCs is influenced by more than just knowledge and experience, and understanding of risk is complex and multifactorial. Out of 252 respondents, the majority were not concerned about the risk of zoonoses (57.5%); however, a considerable proportion (34.9%) was. Overall, 44.0% of respondents reported contracting a confirmed or suspected zoonoses, most frequently dermatophytosis (58.6%). In veterinary professionals who had previous experience of managing zoonotic cases, time or financial constraints and a concern for adverse animal reactions were not perceived as barriers to use of personal protective equipment (PPE). For those working in large animal practice, the most significant motivator for using PPE was concerns over liability. When assessing responses to a range of different “infection control attitudes”, veterinary nurses tended to have a more positive perspective, compared with veterinary surgeons. Our results demonstrate that IPCs are not always adhered to, and factors influencing motivators and barriers to compliance are not simply based on knowledge and experience. Educating veterinary professionals may help improve compliance to a certain extent, however increased knowledge does not necessarily equate to an increase in risk-mitigating behaviour. This highlights construction of risk is complex and circumstance-specific and to get a real grasp on compliance with IPCs, this construction needs to be explored in more depth.